One-Dimensional Heat Transfer in a Convection-Tip Rectangular Thin Fin: A Comparative Study - Fakir, Md Moslemuddin; M. M., Rahman; R. A., Bakar; S., Basri (Universiti Malaysia Pahang, 2010)
Among various numerical solution techniques, finite element method (FEM) and differential quadrature method (DQM) are two important of those. Usually elements are sub-divided uniformly in FEM (conventional FEM, CFEM) to obtain temperature distribution behavior in a fin. Hence, extra computational complexity is needed to obtain a fair solution with required accuracy. In this paper, non-uniform sub-elements are considered for FEM (efficient FEM, EFEM) solution to reduce the computational complexity. Then EFEM is applied for the solution of one-dimensional heat transfer problem in an convection-tip thin rectangular fin. The obtained results are compared with CFEM and efficient DQM (EDQM, with non-uniform mesh generation). It is found that the EFEM exhibits approximately 100% and 99% accuracy compared to CFEM and EDQM respectively showing its potentiality.